Hungarian Monitoring, 19 February 1988 . [Magyar rádiófigyelő], 1988. február 19 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Reagan-Kohl meeting - Schultz's forthcoming Moscow meeting, US-Soviet relations - Soviet initiatives in the Middle Eastern settlement - Czechoslovak corruption scandal Domestic Affairs: - Reform of social security and health insurance - National Council of Trade Unions (SZOT) meeting on the 1988 agricultural plan - Foreign Minister Schultz prepares for Asian and Pacific tour - György Fejti at ELTE - National Health Protection Council: Hungarian is the sickest country in Europe Economy: - Factory directors: protecting the interests of work communities Külpolitika: - Reagan - Kohl találkozó - Schultz közelgő moszkvai látogatása, amerikai - Szovjet kapcsolatok - Szovjet kezdeményezések a közel-keleti rendezés ügyében - Csehszlovák korrupciós botrány Belpolitika: - A társadalombiztosítás és az egészségügy reformja - SZOT ülés a 88-as népgazdasági tervről - Várkonyi külügyminiszter ázsiai és Csendes - Óceáni körútra indul - Fejti György az ELTE-n - Országos Egészségvédelmi Tanács: Magyarország Európa legbetegebb országa Gazdaság: - Ipargazdás: a gazdasági munkaközösségek érdekvédelme